131I‐Meta‐iodobenzylguanidine followed by busulfan and melphalan and autologous stem cell rescue in high‐risk neuroblastoma. Issue 2 (24th October 2020) - Giardino, Stefano; Piccardo, Arnoldo; Conte, Massimo; Puntoni, Matteo; Bertelli, Enrica; Sorrentino, Stefania; Montera, Mariapina; Risso, Marco; Caviglia, Ilaria; Altrinetti, Vania; Lanino, Edoardo; Faraci, Maura; et al.
Abstract: Introduction: Despite the progress in current treatments, the event‐free survival of high‐risk neuroblastoma (HR‐NB) patients does not exceed 40%‐50%, and the prognosis of refractory or relapsed patients is poor, still representing a challenge for pediatric oncologist. Therapeutic Iodine‐131 meta‐iodobenzylguanidine (Th‐ 131 I‐MIBG) is a recognized safe and potentially effective treatment for NB. Materials: This retrospective study reports the outcomes of 28 MIBG‐avid NB patients with advanced disease either refractory or relapsed, which was undertaken from 1996 to 2014. Th‐ 131 I‐MIBG was administered shortly before (median: 17 days) high‐dose chemotherapy with busulfan and melphalan (HD‐BuMel) and autologous stem cell rescue (ASCR) at the Gaslini Institute in Genoa, with the aim of analyzing the feasibility, safety, and efficacy of this approach. Results: Engraftment occurred in all patients after a median of 14 (11‐29) and 30 days (13‐80) from ASCR for neutrophils and platelets, respectively. No treatment‐related deaths were observed. The main high‐grade (3‐4) toxicity observed was oral and gastrointestinal mucositis in 78.6% and 7.1% of patients, respectively, whereas high‐grade hepatic toxicity was observed in 10.7%. Two patients developed veno‐occlusive‐disease (7.1%), completely responsive to defibrotide. Hypothyroidism was the main late complication that occurred in nine patients (31.1%). After Th‐ 131 MIBG and HD‐BuMel, 19 patients (67.8%) showed an improvement in disease status. Over a median follow‐up of 15.9 years, the three‐year and five‐year overall survival (OS) probabilities were 53% (CI 0.33‐0.69) and 41% (CI 0.22‐0.59), and the three‐year and five‐year rates of cumulative risk of progression/relapse were 64% (CI 0.47‐0.81) and 73% (CI 0.55‐0.88), respectively. MYCN amplification emerged as the only risk factor significantly associated with OS (HR, 3.58; P  = 0.041). Conclusion: Th‐ 131 I‐MIBG administered shortly before HD‐BuMel is a safe and effective regimen for patients with advanced MIBG‐avid NB. These patients should be managed in centers with proven expertise.